Pengaruh Pemberian POC Limbah Buah dan Kotoran Kambing Terhadap Pertumbuhan dan Produksi Tanaman Terung Ungu (Solanum melongena) - Hamzah, Ali; Siregar, Maimunah; Lubis, Najla (JURNAL AGROPLASMA, 2025)
The utilization of organic fertilizers can be a solution to reduce dependence on inorganic fertilizers and also contribute to improving the surrounding environmental conditions. This study aims to evaluate the effect of applying fruit waste POC and goat manure fertilizer on the growth of purple eggplant (Solanum melongena L). The experimental design used a randomized block design consisting of two factors. The first factor is the dose of goat manure fertilizer, which includes: K0 (0 kg/plot), K1 (2 kg/plot), K2 (4 kg/plot) dan K3 (6 kg/plot). The second factor is the concentration of fruit waste POC, which includes : B0 (0 ml/L.air/plot), B1 (100 ml/L.air/plot), B2 (200 ml/L.air/plot) dan B3 (300 ml/L.air/plot). The parameters observed in this study include plant height, stem diameter, number of productive branches, number of fruits per plant, number of fruits per plot, weight of fruits per plant, and weight of fruits per plot. The analysis of variance shows that the application of goat manure fertilizer and fruit waste POC did not have a significant effect on plant height, stem diameter, and the number of productive branches. However, there was a highly significant effect on the number of fruits per plant, the number of fruits per plot, the weight of fruits per plant, and the weight of fruits per plot. The interaction between the two treatments did not affect all observed parameters. Keywords: purple eggplant, fruit waste poc, goat manure fertilizer